Pemberdayaan masyarakat Kelurahan Perkamil dalam mengurangi potensi terjadinya banjir - Tiene M.B. Turangan; Suddin Simandjuntak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
In Manado City flood problem is one of the main problem, one of the flood point is in Kelurahan Perkamil. The objective of implementing the appropriate technology for the biopori flood mitigation is one of the solutions empowering the community to (1) reduce the potential for flooding in Manado city, especially Perkamil village. (2) preventing worsening of environmental damage due to water-surface runoff of the ground. The specific targets to be achieved (1) reduce the flow of land surface water from residential or residential areas; (2) Improve soil texture with organic waste material so that the rate of water catchment into the soil increases, this has an impact on the mitigation of water flow runoff and underground water conservation. The implementation method is to conduct training on all head of the environment and some people in the village make Biopori hole, to manage flooding and household waste with biopori technique. the depth of the biopori hole is 100 cm and a diameter of 10 cm. Materials and tools, dirt drill, paralon, and organic waste. The training results of all trainees can make biopori holes, understand their functions and benefits in mitigating flood potential, manage household organic waste and yard. Participants know that the soil can be used as a soil bio composter to produce organic compost that raw materials for household organic waste and yard.